Rambutan (Nephelium lappaceum L.) as a Source of Nutrients and Functional Compounds: An Overview - Indra Marliana; Arum Widyastuti Perdani (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2026)
Rambutan is a tropical horticultural commodity with considerable economic potential and prospects for product development. Its utilization is not limited to fresh consumption but may also be developed into value-added raw materials. This article aims to review the nutritional composition and functional properties of rambutan (Nephelium lappaceum L.) and its potential applications in various sectors. The study employed a literature review method by examining relevant national and international scientific publications, followed by descriptive analysis to obtain a comprehensive synthesis. Rambutan contains water, carbohydrates, protein, and various micronutrients. In addition to the edible pulp, the seed and peel also demonstrate significant potential. Rambutan seeds are rich in fatty acids and protein, while the peel contains high levels of phenolic compounds and antioxidants. Several studies indicate that rambutan peel extract exhibits stronger antioxidant, antimicrobial, and antidiabetic activities compared to other parts of the fruit. These properties highlight its potential applications in the food, cosmetic, and pharmaceutical industries, while also supporting agricultural waste valorization through the utilization of seeds and peels. Keywords: biological activity, functional compounds, nutritional components, rambutan, waste utilization